KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA - Mohammad Ali Rasyid (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
The purpose of writing this article is to discuss mathematical communication skills, ranging from understanding, indicators on measuring mathematical communication skills, models, strategies, variants of questions that can be used to measure mathematical communication skills, and approaches that can be applied to develop them. The conclusion of this article based on the results of a scientific literature review is as follows: (1) Mathematical communication skills consist of oral and written communication. Oral communication in the form of: explaining and discussion, while writing communication in the form of: expressing mathematical ideas by means of equations, tables, images / graphics and with the students' own language. (2) Indicators of mathematical communication skills: mathematical expressions (mathematical expression), written (written text), and drawing (drawing). (3) Types of description questions that can be used to measure mathematical abilities are like applicative, transfer, elaborative, and explorative questions. (4) Types of models and learning approaches that can be used to improve mathematical communication skills are: PMR approach, problem posing learning model with PMR approach, problem solving learning model with PMR approach, and reciprocal teaching.obesity in children is the relationship of genetic factors with the parents, not the share of food intake with energy output being consumed must be issued, and the lack of performing activities the sport has also become another cause factor against obesity it is art learning modules and skills at elementary school students of the country Randusari.